Teachers’ perception of the head of department’s performance and of pedagogical supervision - Abreu, Alice (2019)
Introduction: Within Portuguese schools the Head of Department is an intermediate manager, a supervisor and a leader who must be capable of playing a leading role and demonstrating the appropriate communicative skills so that he can mobilize the teachers who are part of his team to fulfill their educational ideals. For this reason, pedagogical supervision takes on a prominent role in the activities he has to develop. Objectives: To know how teachers at the several levels of education, other than that of Higher Education, perceive head of department’s performance within the current Portuguese school organization and of some factors that can influence that performance, notably the specialized training in pedagogical/instructional supervision. Methods: A descriptive and cross-sectional methodology was used using a survey carried out through the application of a questionnaire. The sample was composed of 106 teachers from all academic departments who were working in a school grouping located in the Viseu district. The data collected were subject to a descriptive and inferential statistical analysis. Results: The teachers seem to value the promotion of an articulated work between the different teachers of the academic department to which they belong and between teachers from different departments, the creation of encouragement actions that would foster a reflection on their teaching practices and an openness to change and innovation. They also consider that the Head of Department should promote collaborative work, as well as generate and share knowledge. However, they state that the Head of Department’s workload and the consequent lack of time to respond to all requests that his position requires may have a negative influence on his performance. Conclusions: The Heads of Academic Department should assume the need for training in their activity to ensure legitimacy and credibility in the most wide-ranging aspects and dimensions, both at a personal/relational level, and at a professional level.